2014
DOI: 10.2527/jas.2014-7885
|View full text |Cite
|
Sign up to set email alerts
|

Healing of surgical castration wounds: a description and an evaluation of flunixin1

Abstract: Previous studies have shown that surgical castration wounds take between 10 and 61 d to heal. The objectives of this work were to describe healing, inflammation, lying behavior, and serum concentration of substance P after surgical castration in beef calves and to evaluate the effect of a possible intervention, a single injection of flunixin meglumine (1.1 mg/kg IV, a NSAID), on the healing process. Calves (mean±SE: 25±2.0 d of age; 54±1.4 kg BW) were surgically castrated with or without an injection of flunix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 30 publications
3
32
0
Order By: Relevance
“…However, to date no studies have been conducted evaluating its efficacy in reducing long-lasting stress and inflammatory pain, inflammation, or healing beyond 1 wk post castration. Mintline et al (2014) did not find a reduction in inflammation or improved rate of healing after the administration of a single dose of flunixin meglumine following castration in beef calves. In addition, there are very few published studies on the effects of subcutaneous (s.c.) meloxicam on mitigating pain in calves younger than 3 mo of age (Creutzinger et al 2017;Meléndez et al 2018a), or on multiple painful procedures conducted concurrently.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…However, to date no studies have been conducted evaluating its efficacy in reducing long-lasting stress and inflammatory pain, inflammation, or healing beyond 1 wk post castration. Mintline et al (2014) did not find a reduction in inflammation or improved rate of healing after the administration of a single dose of flunixin meglumine following castration in beef calves. In addition, there are very few published studies on the effects of subcutaneous (s.c.) meloxicam on mitigating pain in calves younger than 3 mo of age (Creutzinger et al 2017;Meléndez et al 2018a), or on multiple painful procedures conducted concurrently.…”
Section: Introductionmentioning
confidence: 56%
“…Scrotal circumference for KN and KB calves was greater than CN on day 7 and day 14 post castration as a result of the inflammation caused by surgical castration (Molony et al 1995;Stafford et al 2002;Marti et al 2017a). Mintline et al (2014) observed that inflammation peaked 2-3 d post surgical castration, whereas Robb and Wood (1990) and Marti et al (2017b) observed wound swelling up to 14 d after the procedure. In addition, SC of KB calves tended (P = 0.08) to be greater than KN calves the first 14 d post procedure.…”
Section: Itemsmentioning
confidence: 98%
See 1 more Smart Citation
“…This study showed no difference in SUBP between LSH and AH cattle or between NEXH and EXH cattle, but this does not necessarily indicate a lack of pain, as not all studies of painful procedures show a difference in SUBP (Mintline et al, 2014). Also, recent refinements in the assays have led to a change from an ELISA to an RIA method making comparison with results from previous studies that used an ELISA method difficult.…”
Section: Discussionmentioning
confidence: 54%
“…Although NSAIDs may provide analgesic benefit after castration, overall inflammation during healing may not be reduced compared with the cattle not receiving NSAIDs at castration. 22 Inflammation and healing after surgical castration is expected to take on average between 3 and 4 weeks. Contamination is expected; however, infection should be recognized early and treated.…”
Section: Postcastration Complications and Managementmentioning
confidence: 99%